BREAKING BARRIERS: ENGLISH LANGUAGE LEARNING IN SPECIAL EDUCATION SCHOOLS FOR CHILDREN WITH SPECIAL NEEDS - Yulizah, Yosi; Naimah; Munastiwi, Erni; Lubis, Namiroh; Oktori, Agus Riyan (International Journal of Education, Language, and Social Science, 2024)
This research aims to analyze how children with special needs learn English in special education schools, by analyzing pre-learning strategies and the challenges of learning English for children with special needs in Special Schools. This research uses a qualitative descriptive approach, this article aims to identify and analyze English language learning models in special elementary schools. Data was collected through Google Form interviews by considering certain characteristics and situations. In the context of learning English for children with special needs, learning designs are prepared based on an analysis of their learning needs and barriers. By designing appropriate learning, the learning process becomes more structured, and learning objectives can be better achieved. A teacher must have creativity, flexibility, commitment to learning progress, and a willingness to continue learning from his students. emphasizes that a teacher, regardless of field of study, who teaches children with special needs must have a strong scientific understanding of disability, its causes, the assessment process, and its implementation. For English teachers, it is crucial to understand the specific aims or targets of English learning for students with special needs. With a strong grasp of learning objectives, teachers can design suitable learning approaches, models, and strategies.